2015
DOI: 10.3390/mi6121458
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Oil Droplets in a Non-Newtonian Liquid Using a Microfluidic T-Junction

Abstract: Abstract:We have compared the formation of oil drops in Newtonian and non-Newtonian fluids in a T-junction microfluidic device. As Newtonian fluids, we used aqueous solutions of glycerol, while as non-Newtonian fluids we prepared aqueous solutions of xanthan, a stiff rod-like polysaccharide, which exhibit strong shear-thinning effects. In the squeezing regime, the formation of oil droplets in glycerol solutions is found to scale with the ratio of the dispersed flow rate to the continuous one and with the capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
(67 reference statements)
2
21
0
Order By: Relevance
“…In particular, A ∼ ϕ (0.32±0.02) , the exponent being similar to those reported by Refs. [35,63]. These observations provide a direct, experimental evidence of the validity of the Ca number, Eqs.…”
Section: B Rescaling Over Casupporting
confidence: 54%
See 2 more Smart Citations
“…In particular, A ∼ ϕ (0.32±0.02) , the exponent being similar to those reported by Refs. [35,63]. These observations provide a direct, experimental evidence of the validity of the Ca number, Eqs.…”
Section: B Rescaling Over Casupporting
confidence: 54%
“…Images of the droplets are acquired and analyzed in with custom software, which also controls the syringe pumps. The length L of the droplets is measured, after breakup, in a region of interest downstream of the T-junction ( Fig.1-A), and is averaged over at least a hundred droplets [35]. Additional details on the experimental setup are reported in Sec.…”
Section: A Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiarello et al 14 who studied the formation of organic droplets in a T-junction channel using different concentrations of xanthan gum in water, investigated the shear-thinning effect on the droplet size. They compared a xanthan gum/water solution to a glycerol/water (Newtonian) one with similar viscosity and found that the droplet lengths produced in the polymeric mixtures were longer than those obtained in the Newtonian one especially at a high flow rate ratio (under constant continuous phase flow rate).…”
Section: Plug Lengthmentioning
confidence: 99%
“…Arratia et al 13 investigated the filament thinning and breakup of viscoelastic fluids in liquid-liquid flows in a crossslot microchannel inlet to obtain their extensional viscosity. Chiarello et al 14,15 studied the formation of oil droplets in shear-thinning, aqueous solutions and introduced an effective Capillary number that took into account the shear-thinning rheology. They observed that the droplet size in the nonNewtonian fluids increased with the flow rate ratio and decreased with increasing continuous phase flow rate.…”
Section: Introductionmentioning
confidence: 99%